What is a pragmatic theory of meaning? - Wellmer, Albrecht; Montoya Peláez, Jorge (Estudios de Filosofía, 1991)
What does it mean to understand a manifestation? An obvious and plausible answer at first glance would be: It means understanding what a speaker says and how he thinks what he says. The meaning of a manifestation is understood here as the result of two forces: that of the meaning of a sentence and that of the intention of a speaker who wants to say (make understood) something.